Phytochemical Analysis of Anti-Inflammatory and Antioxidant Effects of Mahonia aquifolium Flower and Fruit Extracts. (27th June 2018) - Andreicut, Andra-Diana; Pârvu, Alina Elena; Mot, Augustin Cătălin; Pârvu, Marcel; Fischer Fodor, Eva; Cătoi, Adriana Florinela; Feldrihan, Vasile; Cecan, Mihai; Irimie, Alexandru
Abstract : Oxidative stress and inflammation are interlinked processes. The aim of the study was to perform a phytochemical analysis and to evaluate the antioxidant and anti-inflammatory activities of ethanolic Mahonia aquifolium flower (MF), green fruit (MGF), and ripe fruit (MRF) extracts. Plant extract chemical composition was evaluated by HLPC. A DPPH test was used for the in vitro antioxidant activity. The in vivo antioxidant effects and the anti-inflammatory potential were tested on a rat turpentine oil-induced inflammation, by measuring serum nitric oxide (NOx) and TNF-alpha, total oxidative status (TOS), total antioxidant reactivity (TAR), oxidative stress index (OSI), 3-nitrothyrosine (3NT), malondialdehyde (MDA), and total thiols (SH). Extracts were administrated orally in three dilutions (100%, 50%, and 25%) for seven days prior to inflammation. The effects were compared to diclofenac. The HPLC polyphenol and alkaloid analysis revealed chlorogenic acid as the most abundant compound. All extracts had a good in vitro antioxidant activity, decreased NOx, TOS, and 3NT, and increased SH. TNF-alpha was reduced, and TAR increased only by MF and MGF. MDA was not influenced. Our findings suggest that M. aquifolium has anti-inflammatory and antioxidant effects that support the use in primary prevention of the inflammatory processes.